The Efficacy and Safety of Dotinurad on Uric Acid and Renal Function in Patients with Hyperuricemia and Advanced Chronic Kidney Disease: A Single Center, Retrospective Analysis - Yanai K; Hirai K; Kaneko S; Mutsuyoshi Y; Kitano T; Miyazawa H; Ito K; Ueda Y; Ookawara S; Morishita Y (Dove Medical Press, 2023)
Katsunori Yanai, Keiji Hirai, Shohei Kaneko, Yuko Mutsuyoshi, Taisuke Kitano, Haruhisa Miyazawa, Kiyonori Ito, Yuichiro Ueda, Susumu Ookawara, Yoshiyuki Morishita Division of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, Saitama, JapanCorrespondence: Keiji Hirai, Division of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, 1-847 Amanuma-cho, Omiya-ku, Saitama-shi, Saitama-ken, 330-8503, Japan, Tel +81-48-647-2111, Fax +81-48-647-6831, Email keijihirai@kfy.biglobe.ne.jpObjective: We investigated the efficacy and safety of dotinurad, a selective urate reabsorption inhibitor, in hyperuricemic patients with advanced chronic kidney disease (CKD) (stage G3-5).Patients and Methods: We retrospectively analyzed the cases of 34 patients (mean age, 68.6 ±  13.3 years; 17 men and 17 women) after 12 months of dotinurad treatment based on the changes in uric acid (UA) and the urine protein-to-creatinine ratio (UPCR) plus the annual change in estimated glomerular filtration rate (eGFR). Hyperuricemia (UA ≥ 6.0 mg/dL) and advanced CKD (mean eGFR: 32.0 ± 13.3 mL/min/1.73m2; stage G3, n=17; G4, n=13; G5, n=4) were present in all of the patients. The cases of 34 matched individuals with similar propensity scores (who were not taking dotinurad) were analyzed as a control group.Results: UA values decreased significantly in the dotinurad group (7.1 ±  0.8 mg/dL to 5.9 ±  1.0 mg/dL, p< 0.05) but those did not change in the control group. UPCR did not change in either group. Low-density lipoprotein cholesterol also decreased significantly in the dotinurad group (98.8 ±  43.4 mg/dL to 82.9 ±  33.1 mg/dL, p< 0.05). With the 12-month dotinurad treatment, the annual change in the patients' eGFR was significantly improved from − 6.0 ±  12.9 mL/min/1.73 m2/year to − 0.9 ±  4.6 mL/min/1.73 m2/year (p< 0.05), but there was no change in the control group.Conclusion: Dotinurad can decrease UA levels and might attenuate renal function decline in individuals with hyperuricemia and advanced CKD.Keywords: chronic kidney disease, dotinurad, hyperuricemia, uric acid, renal function